Central venous catheter‐related complications in hematologic patients: An observational study. Issue 4 (24th December 2021) - Rockholt, Mika M.; Thorarinsdottir, Hulda R.; Lazarevic, Vladimir; Rundgren, Malin; Kander, Thomas
Abstract: Background: The frequency of central venous catheter (CVC)‐related complications in hematologic patients has previously been studied but some uncertainty remains. Therefore, this observational cohort study was designed primarily to investigate mechanical and infectious complications related to CVC insertion in hematologic patients and secondarily to identify factors associated with these complications. Methods: Documented data on CVC insertions in all adult hematologic patients who received a CVC from 2013 to 2019 at a University Hospital in Sweden were retrospectively collected. Results: A total of 589 CVC insertions in 387 patients were included. The prevalence of moderate and severe mechanical complications, predominantly comprising grades 2–4 bleeding, was 11%. Preprocedural coagulopathy, number of needle passes, and arterial puncture were all independently associated with grades 2–4 bleeding. The incidence of suspected catheter‐related infections (sCRI) was 3.7/1000 catheter days. Higher body mass index and male gender were independently associated with sCRI. Conclusions: Patients with hematologic malignancies have a high risk of both grades 2–4 bleeding and sCRI after CVC insertion. This underlines the importance of optimizing the conditions at the insertion and also of daily inspections, evaluation of future needs, and extra precautions to avoid sCRI in these susceptible patients.